2015
DOI: 10.22256/pubvet.v8n7.1697
|View full text |Cite
|
Sign up to set email alerts
|

Uso de enriquecimentos ambientais como mitigadores de comportamentos anormais: uma revisão

Abstract: ResumoEsta revisão apresenta conceitos referentes à problematização do ambiente de cativeiro. O objetivo foi analisar a forma com a qual a utilização de enriquecimentos ambientais tem contribuído no desempenho natural de animais cativos. Conclui-se que essa técnica reduz o estresse, aumentando o grau de bem-estar e, consequentemente, estimulando o desenvolvimento de comportamentos típicos da espécie.Palavras-chave: Bem-estar, comportamento, enriquecimento ambiental.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
1
0
Order By: Relevance
“…The difficulty of publishing negative or neutral research is widely known and recognised [ 51 , 52 ]. Other studies also showed the success of the EE technique for animals kept under human care in improving animal welfare by reducing the stress they are exposed to [ 53 , 54 ]. These results may indicate the real efficiency of EE in improving animal welfare or the lack of publications on the negative or neutral effects of this technique.…”
Section: Discussionmentioning
confidence: 99%
“…The difficulty of publishing negative or neutral research is widely known and recognised [ 51 , 52 ]. Other studies also showed the success of the EE technique for animals kept under human care in improving animal welfare by reducing the stress they are exposed to [ 53 , 54 ]. These results may indicate the real efficiency of EE in improving animal welfare or the lack of publications on the negative or neutral effects of this technique.…”
Section: Discussionmentioning
confidence: 99%
“…Além disso, o uso de estratégias de entretenimento, a partir do uso de brincadeiras ou propostas cognitivas de maior complexidade, também favorece a adequação do ambiente de cativeiro, proporcionando o bem-estar dos animais (15) . O enriquecimento ambiental, área do comportamento animal reconhecida por Yerkes e Hedinger na primeira metade do século XIX, estuda a importância do ambiente físico e social para o bem-estar de animais cativos ao fornecer artifícios que permitem que estes expressem o comportamento natural da espécie (16)(17)(18) . Essa técnica consiste em incorporar elementos ao cativeiro que possam reproduzir o habitat natural da espécie, possibilitando que os animais exerçam atividades comuns da vida livre, como locomoção, forrageamento, construção de abrigos, entre outros.…”
Section: Introductionunclassified
“…Environmental enrichment, a field of animal behavior recognized by Yerkes and Hedinger in the first half of the 19 th century, studies the importance of the physical and social environment for the welfare of captive animals by providing elements that allow them to express the natural behavior of the species (16)(17)(18) . This technique consists of incorporating elements into captivity that can reproduce the natural habitat of the species, allowing the animals to exercise common activities of the wild, such as locomotion, foraging, and sheltering, among others.…”
mentioning
confidence: 99%